DEVELOPING AN ARGUMENT-BASED SCIENCE TEXTBOOK FOR JUNIOR HIGH SCHOOL STUDENTS TO IMPROVE STUDENT’S CRITICAL THINKING DISPOSITION AND CRITICAL THINKING SKILL - Sudiana, I Ketut (LPPM Undiksha, 2018)
This study was aimed at producing an argument-based science teaching textbook for junior high school students to improve student’s critical thinking disposition and critical thinking skill. This text book was produced by following Borg and Gall’s (1983). Research and development model for three years. The first year research collected information (need analysis) used to design the draft of the product in the form of argument-based science text book for junior high school to improve student’s disposition and critical thinking skill. The product of the first year research was in the form of a draft of the argument-based science textbook. The second year research tried out the argument-based science text book for junior high school in a limited scope, conducted in three SMP’s in Bali province. This try-out used pretest-posttest one group design. The number of students involved in the second year research was 88 students. The result of the second year research showed that the argument-based science text book for junior high school could improve students’ disposition skill by 21.48% and critical thinking skill by 57.22%. The third year research tried out the argument-based science text book for junior high on a large scale in three SMP’s in Bali province. The study used the pretest–posttest one group design. The number of students involved was 194 students, the control group and experiment group had 97 students respectively. As the comparison the text book entitled Buku Ajar IPA SMP Kurikulum 2013 was used. The data obtained from this third year research were in the form of scores for critical thinking disposition and critical thinking skill. These data were analyzed using multivariate covariance analysis at 5% level of significance. The large scale tries out in the third year was aimed at determining the effectiveness of the argument-based science teaching textbook for junior high school to improve student’s disposition and critical thinking skill. The results showed that there was a significant effect of the argument-based science teaching text book for junior high school students to improve student’s disposition and critical thinking skill on the student’s critical thinking disposition and critical thinking skill both simultaneously and partially or individually. Based on the test of means difference, the argument-based science teaching text book for junior high school students was better than Buku Ajar IPA SMP Kurikulum 2013 in improving the student’s critical thinking disposition and critical thinking skill both simultaneously and partially.